Type and Duration of Mask Use Related To Acne Vulgaris During The Pandemic Period - Dwi Rahmatul Adha Ghozali; Retno Indrastiti; Kanti Ratnaningrum (Universitas Nahdlatul Ulama Surabaya, 2022)
The masks' use has been a suggested strategy to counter COVID-19 transmission throughout this disease outbreak; however, wearing masks tightly closed for an extended period can cause acne vulgaris. The mask's form and duration of use are two factors that may affect the occurrence of acne vulgaris. Therefore, more research is needed to determine the impact of using masks on the prevalence of acne vulgaris. This study aimed to analyze the relationship between the type and duration of mask use and the prevalence of acne vulgaris in the citizens of Kawistowindu Village during the pandemic. This study used an analytical-observational study with a cross-sectional approach, with a sample of 63 people who met the inclusion and exclusion criteria throughout the neighborhood of RT.02 RW.01 Kawistowindu Village. The sample was chosen using a simple random sampling technique. Questionnaire forms, history-taking instruments, and physical examination techniques were used to collect data—the analysis used the Chi-Square test. The results showed that during the pandemic era, there was a significant correlation between the type of mask and the duration of mask use with the occurrence of acne vulgaris (p=0.000; p=0.004). In conclusion, in the pandemic era, the mask form and duration of mask use could be linked to acne vulgaris